Evaluation of karate education and training center student coaching program: bibliometric analysis and Physical Condition - Afifah Bulandari; Johansyah Lubis; Yasep Setiakamawijaya (Indonesian Journal of Sport Management, 2025)
Background: The development of karate as both a competitive and educational sport highlights the importance of systematic athlete training programs supported by scientific evaluation. However, research in the Indonesian context, particularly at the undergraduate level, has often been limited to descriptive studies, creating a gap between academic research and the practical needs of athlete development. Purpose: This study aimed to evaluate the karate training program at the Student Education and Training Center (Pusat Pendidikan dan Latihan Mahasiswa, PPLM) Universitas Negeri Jakarta while simultaneously mapping the trends of undergraduate theses in the Sports Science Program between 2011 and 2022 through bibliometric analysis. Methods: A quantitative descriptive-comparative design was employed, involving 804 theses as bibliometric data and eight karate athletes as participants in physical fitness testing. Data collection included keyword extraction and network visualization using VOSviewer, as well as standardized field tests for flexibility, speed, muscular endurance, power, and aerobic capacity. Statistical analysis was performed with Friedman and Wilcoxon tests using SPSS version 25. Results: Bibliometric findings showed that “physical activity” appeared 88 times and “sports nutrition” 97 times, confirming their dominance as research themes, while performance-focused topics remained below 20 occurrences. Athlete testing revealed an increase in flexibility from 14.8 cm to 20.9 cm, muscular endurance from 43 to 51 push-ups, and power from 52.0 cm to 59.5 cm in vertical jump. Conversely, speed showed only a marginal change (2.99 to 2.92 s), and aerobic endurance remained stable (46.6 to 46.5 levels). Conclusion: These outcomes suggest that current training methods are effective in enhancing flexibility, muscular endurance, and power but less so for speed and aerobic endurance. The study contributes by integrating program evaluation with bibliometric mapping, bridging academic research and athlete training, and reinforcing the scientific foundation of sports development in Indonesia.